The Jrecan Device: Preclinical Data of a Novel Thrombectomy Device in Acute Thromboembolism Model of Beagle Dogs - Li, Chen; Zhou, Ji; Zhang, Yi-Qun; Lv, Jin; Zhang, Ying-Ying; Qiu, Han-Cheng; Liu, Ao-Fei; Jiang, Wei-Jian (Frontiers in Neurology, 2022)
Objective The aim of this study is to investigate the safety and efficiency of a Jrecan® flow restoration system, a novel thrombectomy device, in an arterial thromboembolic occlusion model of Beagle dogs. Methods A total of 12 Beagle dogs with acute thromboembolism were randomized to receive mechanical thrombectomy with either Jrecan® flow restoration device or TrevoTM PROVUE Device (2:1). The efficacy and safety of the two devices, including recanalization rate, the presence of distal embolism, vasospasm, vessel perforation, and vessel injuries were evaluated through DSA and microscopic examination. Result A 100% recanalization rate (mTICI 2b/3) was achieved in both groups. Endothelial and subendothelial injuries occurred in all target vessels. Focal disruption of internal elastic lamina was observed in 4 cases. The mean vessel injury score of the Jrecan® group was 1.16 ± 0.48, significantly lower than that of the TrevoTM group (1.54 ± 0.8) (P < 0.001). Conclusion The Jrecan® and TrevoTM devices demonstrated an equally high recanalization rate in Beagle dogs with acute thromboembolism. However, histological findings revealed that the Jrecan® stent seemed to be safer than the TrevoTM device during clot retrieval, which might be related to a more appropriate radial force provided by the Jrecan® stent that resulted from its wider cell design.